2017
DOI: 10.1021/acs.chemmater.7b00690
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Enhanced Atomic Layer Deposition of Silver Using Ag(fod)(PEt3) and NH3-Plasma

Abstract: A plasma-enhanced atomic layer deposition (ALD) process using the Ag(fod)(PEt 3 ) precursor [(triethylphosphine) (6,6,7,7,8,8,8-heptafluoro-2,2-dimethyl-3,5octanedionate)silver(I)] in combination with NH 3 -plasma is reported. The steady growth rate of the reported process (0.24 ± 0.03 nm/cycle) was found to be 6 times larger than that of the previously reported Ag ALD process based on the same precursor in combination with H 2 -plasma (0.04 ± 0.02 nm/ cycle). The ALD characteristics of the H 2 -plasma and NH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
4
21
0
Order By: Relevance
“…The results on a detailed study of the composition of the ALD Ag NPs by XPS showed that they contain a small amount of oxygen, carbon, fluorine, and phosphorus in the form of precursor residues. Similar results for ALD coatings were obtained earlier by other researchers [ 16 , 24 , 25 ]. However, the presence of such impurities does not noticeably affect the antibacterial properties of silver [ 34 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results on a detailed study of the composition of the ALD Ag NPs by XPS showed that they contain a small amount of oxygen, carbon, fluorine, and phosphorus in the form of precursor residues. Similar results for ALD coatings were obtained earlier by other researchers [ 16 , 24 , 25 ]. However, the presence of such impurities does not noticeably affect the antibacterial properties of silver [ 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…In view of the above, it was necessary to find another way to increase the amount of Ag(fod)(PEt 3 ) entering the reactor to achieve optimal conditions for silver synthesis. The literature analysis showed [ 24 ] that it is useful to conduct several successive pulses of Ag(fod)(PEt 3 ) in one ALD cycle. In our study, we tested regimes with 1, 3, 5, and 7 pulses of 4 s each ( Figure 1 b, normal pulses).…”
Section: Resultsmentioning
confidence: 99%
“… 69 71 Notably, the role of N-containing surface species has previously been addressed for the ALD of Pt and Ag using N 2 or NH 3 plasmas. 19 , 72 , 73 Specifically, N-containing species were proposed to adsorb during the N 2 or NH 3 plasma exposures and to react with the precursor during the subsequent precursor dose.…”
Section: Discussionmentioning
confidence: 99%
“…0.6 V, such as noble metals and platinum group metals, are highly unstable. As a result of this, among others, Pt, Ir, and Ag have been deposited in their metallic state. Finally, while species with intermediate potentials such as W can be deposited as nitrides, the latter have limited thermodynamic stability and decompose at temperatures below 1000 °C.…”
Section: Introductionmentioning
confidence: 92%